The Cowardly Jew they Forgot to Gas: The Phenomenon of Dutch Post-liberation Antisemitism and Some Continuities - Gans, Evelien (Historein, 2019)
This article elaborates on two antisemitic stereotypes or phenomena that show how the Shoah was turned against the Jews as early as 1945. The curse “they forgot to gas you” popped up immediately after the war, during all kind of public rows on the street with Jewish employers and neighbours. It was, so to say, the first antisemitic post-Holocaust stereotype that sent the Jewish survivor – verbally – to the gas chamber. Several Jews took cases to court. The insult “they forgot to gas you” was taken more seriously by Jews themselves and punished more severely by the court than the simple insult “filthy Jew”. The identification of “the Jew” and the gas chamber never disappeared but lives on – also within the football world, satire and anti-Israel demonstrations. It is a manifestation of what Theodor Adorno coined Schuld- und Erinnerungsabwehrantisemitismus (antisemitism based on a rejection of guilt and unwelcome memories). The same goes for the accusation that, during the German occupation, the Jews had offered no, or not enough, resistance against the Nazis. Others had to fight for them. Jews were neither fighters nor heroes; they depended on the courage of gentiles. Also this stereotype of the passive, obedient Jew would persist, for example, in a final school examination paper in 1983 and in some recent Dutch historiography on the Second World War and the Shoah. In this way the Shoah functioned as a point of fixation for postliberation – and more generally – postwar antisemitism.